Reflections of Coaches’ Behaviours on Athletes and Teams in the Scope of Fair Play - GÖRGÜT, İlyas (International Journal of Holistic Health, Sports and Recreation, 2023)
It was aimed to determine the athletes’ views on coaching behaviours within the scope of fair play with this research. The study was prepared with qualitative research method and phenomenology design was preferred from qualitative research designs. The sampling group of the study consists of 12 athletes determined by the easily accessible case sampling method, one of the purposeful sampling methods. Individual interviews were conducted with the athletes within the scope of semi-structured interview technique lasting an average of 20 minutes. The participants were informed that the interview would be recorded and then the records would be transcribed, the necessary permissions were obtained, and in this way, interviews were conducted by creating a suitable environment for the interviews. Descriptive and content analysis methods were applied to the transcribed participant statements. As a result of the analyses, the athletes stated that the coach’s fair play approach and behaviour in accordance with fair play will contribute to the communication within the team and the training environment with a positive atmosphere, that different results will occur if the coach provides equality or does not provide equality between the athletes in terms of athlete performance and that they are in intensive communication within the scope of team integration, creating a family environment and socialisation for their friends who have problems. The fact that those who have duties within the scope of regulating and implementing sports activities establish environments that encourage and improve the behaviours of coaches and athletes within the scope of fair play and supervise the display of the demanded actions will ensure that sportive activities are carried out fairly and in line with the objectives.